الرؤية الإسلامية المقاصدية للمفاوضات السياسية: دراسة تحليلية للمفاهيم النظرية العامة = Political negotiations from the maqasidi perspective: an analytical study of general theoretical concepts = Perundingan politik dari perspektif Maqasid: kajian analitik dalam konsep teori umum - Zaroum, AbdulHamid Mohamed Ali; Rashid, Nasir Abdullatif (IIUM Press, International Islamic University Malaysia, 2020)
تتعرض هذه الدراسة لبيان ضرورة عملية التفاوض في شتى مجالات الحياة، سيما المتعلقة بالمفاوضات السياسية بين الدول والمجتمعات والجماعات، وذلك استنادا إلى مقاصد الشريعة الإسلامية، ومن جملة ما ترمي إليه الدراسة تفعيل دور الفقه السياسي في معالجة بعض النوازل وفق المقاصد الشرعية. ومن أبرز المحاور التي تم التركيز عليها: معاني المفاوضات وأهميتها، وعناصر المفاوضات وخصائصها، ومبادئ التفاوض ونظرياته، ومشروعية المفاوضات وضوابطها الشرعية ومقاصدها العامة، وذلك باستخدام مناهج ثلاثة: المنهج التحليلي لدراسة الإشكالات العلمية المختلفة المرتبطة بالتفاوض، والمنهج الاستقرائي لاستنطاق النصوص؛ لمعرفة مقاصدها، وتنزيلها على مستجدات واقعنا المعاصر، إضافة إلى المنهج التاريخي، وذلك من خلال جمع وتوثيق المعلومات التاريخية المتعلقة بالمفاوضات كالعوامل التي أثرت فيها، والظروف التي أحاطت بها. ومن النتائج التي توصلت إليها الدراسة، أن ثمة ترابطا بين المعاني اللغوية لمفهوم المفاوضات ومفاهيمها الاصطلاحية، وأن لعملية التفاوض ضوابط شرعية عديدة، أهمها ارتباطها بمصلحة غير ملغاة، وأن لا تتعارض مع ضرورة شرعية، فتبطلها، أو تقدمها على مرتبة أعلى منها دون سند شرعي أو عقلي سليم. من أهم مقاصد المفاوضات التعارف، والإقناع، والتعاون على البر والتقوى، والإصلاح بين المتخاصمين، والسلامة في الدين، والنفس، والعقل، والنسل، والمال والوصول بالخصم إلى الحق بطريق لا ينكره هو. ******************************************************************************** This study aims to highlight the Maqasidi perspective in the negotiation process in various domains of life, especially the political negotiation between states, societies and organizations. The activation of the role of Political Jurisprudence in addressing some of the contemporary issues has been one of the main concerns of this short study. Among the most prominent aspects that were focused on: the meanings and importance of negotiations, their elements, theories, legality and general purposes as well as characteristics and principles of negotiations according to the Objectives of Shari’ah. Three approaches have been applied here namely; the analytical approach to study the various scientific problems that are related to negotiations, and the inductive approach for examining and scoping the texts to know their purposes so that they can be adopted in the developments of our contemporary reality, in addition to the historical method which has been used in collecting and documenting historical information related to negotiations such as the factors that affected them, and the circumstances that surrounded them. Among the findings of the study, is that noticeably there is a correlation between the linguistic meanings of the concept of negotiations and their idiomatic concepts, and that the negotiating process has some Shariah regulations and controls the most important of which is their association with interests that are not Islamically rejected and that they do not contradict a necessity considered by Islamic Law, nullify it, or prioritize it over a higher rank interest “Maslahah” than it without legal and logical support. Persuasion, cooperation on righteousness and piety, reconciliation between the litigants, safety in religion, life, intellect, lineage and wealth, are among the most significant purposes of negotiations. ******************************************************************************** Kajian ini menunjukkan perlunya proses perundingan dalam berbagai bidang kehidupan, terutama yang berkaitan dengan perundingan politik antara negara, kelompok dan organisasi.Ini berdasarkan tujuan undang-undang Islam, dan antara tujuan kajian ini adalah untuk mengaktifkan peranan perundangan politik dalam menangani beberapa perkara sesuai dengan tujuan yang sah. Antara paksi paling menonjol yang diberikan tumpuan adalah pada makna, kepentingan, elemen serta ciri rundingan, teori berkaitan, kesahihan rundingan dan kawalan undang-undang serta tujuan umumnya. Terdapat tiga pendekatan yang digunapakai: pendekatan analitik untuk mengkaji pelbagai masalah saintifik yang berkaitan dengan rundingan, pendekatan induktif untuk menyoal teks; untuk mengetahui maksudnya, serta memuat turunnya ke perkembangan realiti kontemporari, selain daripada kaedah sejarah, untuk mengumpul dan mendokumentasikan maklumat sejarah yang berkaitan dengan rundingan, seperti faktor-faktor yang mempengaruhi, dan keadaan di sekitarnya. Di antara hasil kajian ini, terdpat kaitan antara makna linguistik konsep perundingan dan konsep idiomatiknya, begitu juga, bahawa proses perundingan mempunyai banyak kawalan hukum, yang paling penting adalah kaitannya dengan kepentingan yang tidak dibatalkan, dan bahawa ia tidak bertentangan dengan keperluan undang-undang, sehingga membatalkannya, atau membawanya pada tahap yang lebih tinggi daripada itu tanpa sokongan undang-undang yang sah. Antara tujuan perundingan yang paling penting adalah berkenalan, meyakinkan, bekerjasama dalam kebenaran dan ketakwaan, pembaharuan antara para pengadu, integriti dalam agama, diri, fikiran, keturunan, wang dan akses kepada lawan kepada kebenaran dengan cara yang tidak dinafikan.